2020
DOI: 10.1002/mp.14402
|View full text |Cite
|
Sign up to set email alerts
|

Full‐count PET recovery from low‐count image using a dilated convolutional neural network

Abstract: Purpose: Positron emission tomography (PET) is an essential technique in many clinical applications that allows for quantitative imaging at the molecular level. This study aims to develop a denoising method using a novel dilated convolutional neural network (CNN) to recover full-count images from low-count images. Methods: We adopted similar hierarchical structures as the conventional U-Net and incorporated dilated kernels in each convolution to allow the network to observe larger, more robust features within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…38 Likewise, a recent network architecture has been proposed that replaces down/upsampling in encoder-decoder architectures with dilated convolutions (dNet). 39 The consistent change in image resolution from down/upsampling layers leads to a degree of blurring, which may result in smoothed edges. Therefore, incorporating the dNet architecture, which utilizes dilated kernels to increase receptive field size, may be of use to alleviate the problem of smoothed edges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Likewise, a recent network architecture has been proposed that replaces down/upsampling in encoder-decoder architectures with dilated convolutions (dNet). 39 The consistent change in image resolution from down/upsampling layers leads to a degree of blurring, which may result in smoothed edges. Therefore, incorporating the dNet architecture, which utilizes dilated kernels to increase receptive field size, may be of use to alleviate the problem of smoothed edges.…”
Section: Discussionmentioning
confidence: 99%
“…Disparity estimation is a method that uses weighted average operation on the probability distribution to determine segmentations; this method has been shown to alleviate the problems of preserving local structure of edge boundaries 38 . Likewise, a recent network architecture has been proposed that replaces down/upsampling in encoder‐decoder architectures with dilated convolutions (dNet) 39 . The consistent change in image resolution from down/upsampling layers leads to a degree of blurring, which may result in smoothed edges.…”
Section: Discussionmentioning
confidence: 99%
“…Sanaat et al [ 80 ] compared low-dose to full-dose mappings with a 3D Unet in image space and sinogram space and demonstrated that sinogram space processing produced improved results with significantly higher PSNR and significantly lower SUV bias. Spuhler et al [ 79 ] used a CNN formulation with dilation of the convolutional kernels in place of down-sampling operations, with PSNR, SSIM and NRMSE results comparable to a Unet. Wang et al [ 81 ] trained a feed-forward fully connected network with synthetic data to denoise low-dose 4 × 4 × 4 pixel patches and directly applied the network to 82 Rb cardiac PET images.…”
Section: Review Of Deep Learning-based Low-dose To Full-dose Post-pro...mentioning
confidence: 99%
“…Such a network lacks sufficient knowledge to distinguish noise from useful information. Adjacent slices can be used as different input channels [PET-plus-MR or PET-only image input (165,166), three-layer PET image input (167,168), and five-layer SPECT image input (124,125)] can provide 2.5D structural information to the network, and this can be called a method of target feature enhancement. Compared with 3D convolution, calculation costs are high for this approach.…”
Section: Low-dose Imagingmentioning
confidence: 99%